SOCIAL MEDIA AS A TOOL FOR SELF-AWARENESS SEARCH THROUGH YOUTUBE CONTENT RINTIK SEDU - Baqita, Jinantiya (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Abstract This research examines the role of social media, especially YouTube, in the process of searching for self-awareness of the younger generation using a case study of Rintik Sedu's YouTube content. By involving six informants as followers of Rintik Sedu and conducting in-depth interviews, this study found that Rintik Sedu's Youtube content plays an important role in helping young people recognize their strengths and weaknesses, provide new perspectives on life problems, and motivate them to be more grateful. Interesting visualizations, long duration, and relevance to the lives of the younger generation are the main attractions of this content. The main reason why netizens choose Rintik Sedu content is because the content is very relatable and relevant to the reality of their lives and is delivered in an interesting and accessible style. These findings support previous research on the relationship between social media and self-concept and provide insights for content creators in designing content that supports the audience's search for self-awareness.